(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Although the liver is not a primary hematopoietic site after the period of embryogenesis, however liver diseases in human can have adverse effects on hematopoiesis. This study evaluated the ability of Vitex angus-castus extract to ameliorate hematopoietic alteration occasioned by carbon tetrachloride (CCl4) induced acute liver injury. Varying doses of V. angus-castus plant extract were administered to groups of rats with CCl4 Induced acute liver injury. The low dose group (LEL) had 200mg/Kg body weight; the medium dose (MEL) had 400 mg/kg while the high dose group (HEL) had 600 mg/Kg of the extract once daily for 21 days. Each group had composite control without liver injury ie LE, ME and HE. The packed cell volume (PCV), hemoglobin concentration (Hb%), red blood cell count (RBC), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) and mean corpuscular hemoglobin (MCH) were similar across the groups. Groups LEL and ME had significantly elevated white blood cell count (WBC). Amongst the composite groups ie LE: LEL; ME:MEL; & HE:HEL, there was significant difference within the composite group. The WBC differential was lymphocyte predominant without significant difference. The two low extract groups (LE & LEL) had significant thrombocytopenia ie low platelet count. The ethanolic extract of V. angus-castus only affects the white cell and platelet components of the blood and not the erythrocyte parameters